Upaya Pencegahan Covid-19 dengan Vaksinasi Massal - Ivanna Beru Brahmana; Iman Permana (Universitas Mathla'ul Anwar Banten, 2023)
Vaksinasi Covid-19 memberikan harapan baru dalam upaya pencegahan Covid-19. Masyarakat digerakkan turut aktif mendatangi pelayanan kesehatan yang membuka vaksinasi massal. Universitas Muhammadiyah Yogyakarta turut berperan aktif membuka pelayanan vaksinasi massal. Tujuan: Meningkatkan animo masyarakat mengikuti vaksinasi pencegahan Covid-19. Metode: Pemberian vaksinasi Covid-19 secara massal dengan sistem drive thru dilakukan pada tanggal 23 Agustus 2021 di pelataran kampus UMY, menjaring peserta sebanyak jumlah vaksin yang tersedia. Vaksinator adalah para dosen dari Fakultas Kedokteran & Ilmu Kesehatan (FKIK UMY), terbagi dalam sesi pagi dan siang, yang akhirnya sebanyak 19 dosen bertindak selaku vaksinator. Kesiapan alat & vaksin difasilitasi oleh pihak Divisi Kesehatan Polda DIY dan panitia universitas. Hasil: Jumlah peserta yang berhasil disuntik vaksin sebanyak 2.597 orang. Peserta datang melalui tiga jalur: jalan kaki, naik sepeda motor, dan naik mobil. Setiap jalur tersedia vaksinator yang siap memberikan penyuntikan vaksin. Bersamaan dengan penyuntikan vaksinasi, para peserta diminta pendapat mereka tentang pelaksanaan vaksinasi. Seluruh peserta menyatakan puas dengan pelaksanaan vaksinasi yang berjalan lancar, simpel, tidak ribet mulai dari pendaftaran hingga evaluasi pasien pasca penyuntikan. Mereka juga menyatakan besarnya manfaat kegiatan pengabdian dalam upaya mempercepat pelaksanaan vaksinasi Covid-19 di masyarakat. Kesimpulan: Pelaksanaan vaksinasi drive thru meningkatkan animo masyarakat untuk mengikuti vaksinasi pencegahan Covid-19. Covid-19 vaccination provides new hope in the prevention of Covid-19. The community is mobilized to actively participate in visiting health services that open mass vaccinations. Universitas Muhammadiyah Yogyakarta as a vehicle for the academic community to take an active role in opening mass vaccination services. Objective: to increase public interest in participating in Covid-19 prevention vaccinations. Method: Mass distribution of Covid-19 vaccination using a drive thru system on campus was done on the 23rd of August 2021, by attracting as many participants as possible according to the number of vaccines provided. The vaccinators are lecturers from the Faculty of Medicine & Health Sciences (FKIK UMY), which are divided into 2 sessions, morning and afternoon, with 19 lecturers acted as vaccinators. The preparation of equipment & vaccines is facilitated by the university committee. Results: The number of participants who were successfully injected with the vaccine was 2597 people. Participants came through three routes: walking, motorbike, and car with available vaccinators according to the number of lines Simultaneously with the injection of the vaccination, the participants were asked for their opinion on the implementation of the vaccination. All participants expressed satisfaction with the implementation of the vaccination which went smoothly, simple, and not complicated from registration to evaluation of patients after injection. They also stated the magnitude of the benefits of community service activities in an effort to accelerate the implementation of Covid-19 vaccination in the community. Conclusion: The implementation of the drive thru vaccination increases the public's interest in participating in the Covid-19 preventive vaccination.